(untitled) (Research, Society and Development, 2021)
Brazil is among the main producing and exporting countries of papaya (Carica papaya Linnaeus). Papaya is one of the most important fruits in the Brazilian economy and food, with countless industrial possibilities and nutritional, pharmacological and medicinal applications. However, its production in the country has particular aspects, which influence scientific research on the fruit, as well as the national and world consumer market. This study consists of a literature review on aspects and peculiarities of papaya production in Brazil. A brief history of papaya was included; general characteristics of the papaya plant and the papaya fruit; consumption characteristics and industrial applicability of the fruit; commercial production in Brazil; main hybrid cultivars used and risk factors for production, especially viral diseases of economic impact; aspects of the genetic improvement of papaya in Brazil; the limitations of transgenics in the country and new strategies suggested. From the set of information in this study, applied research on new technologies to maintain papaya productivity in Brazil is considered necessary. Therefore, it is suggested to carry out genetic research on the hybridization of commercial cultivars used with wild papaya varieties from South America and/or Central America.